Digital sport for performance enhancement and competitive evolution intelligent gaming technologies - Pope, Nigel; Kuhn, Kerri-Ann L.; Forster, John, 1946-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
An unacknowledged, global phenomenon in the sphere of computer applications, digital sport, plays an enormous part in training and performance enhancement. This publication provides an overview of the increasing level of digitization in sport including areas of gaming and athlete training. It discusses sport consumers and the playing of computer games, drawing from academicians and practitioners from varied disciplines and approaches.
Digital technologies and the intensification of economic and organisational mechanisms in commercial sport -- A general-purpose taxonomy of computer-augmented sports systems -- Dynamics and simulation of general human and humanoid motion in sports -- Technologies for monitoring human player activity within a competition -- Video-based motion capture for measuring human movement -- Technology to monitor and enhance the performance of a tennis player -- Quantitative assessment of physical activity using inertial sensors -- Computer supported collaborative sports: an emerging paradigm -- Digital sport: merging gaming with sports to enhance physical activities such as jogging -- Double play: how video games mediate physical performance for elite athletes -- A league of our own: empowerment of sport consumers through fantasy sports participation -- Computational and robotic pool -- A framework for the adoption of the internet in local sporting bodies: a local sporting association example -- Online questionnaires and interviews as a successful tool to explore foreign sports fandom -- Virtual digital Olympic museum -- The market structure and characteristics of electronic games -- Sport video game sponsorships and in-game advertising -- In-game advertising: effectiveness and consumer attitudes -- The effect of arousal on adolescent's short-term memory of brand placements in sports advergames -- Schemas of disrepute: digital damage to the code.
Includes bibliographical references (p. 336-376) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 26, 2010).
Keywords: Sports -- Technological innovations; Performance technology; Sports sciences; Video games; Computer games; Computer supported collaborative sports; Digital sport; Intelligent gaming technologies; Measuring human movement; Merging gaming with sports; Monitoring human player activity; Performance enhancement; Quantitative assessment of physical activity; Simulation of general human and humanoid motion; Training and participation applications; Video-based motion; Video games for physical performance; Electronic books